Unusual Thermo‐Enhanced Second Harmonic Generation in Organic Configurationally‐Locked Polyene Crystals - Yi Liu; Pengfei Zhu; Qingshun Fan; Zihao Zhao; Linjie Wei; Yu Ma; Haojie Xu; Wuqian Guo; Junhua Luo; Zhihua Sun (Advanced Science)
Abstract To modulate nonlinear optical (NLO) effects of crystalline material holds great application potential in the photoelectronic and optical fields. Organic configurationally‐locked polyene represents an exciting NLO family with large second harmonic generation (SHG) effects, whereas it is a huge blank to switch and modulate their NLO property through external stimuli. For the first time, here present unusual thermo‐enhanced SHG activities are presented in a polyene‐based NLO compound, 2‐{3‐[2‐(4‐pyrrolidinphenyl)vinyl]‐5,5‐dimethylcyclohex‐2‐enylidene}malononitrile (1), giving a record‐high magnitude of SHG enhancement up to ≈170% during its isomorphic phase transition. Theoretical analysis discloses this behavior stems from the reduced degree of torsion in the π‐conjugated structures in 1, as verified by dihedral angles between its pyrrolidine and phenyl planes. As the first study on thermo‐enhanced SHG properties of organic crystals, this work affords a new avenue of modulating physical properties to fabricate high‐performance photoelectronic and optical devices.